14 : ( 4 2/ 3 - 1 5/9 ) + 14 : 2/ 5 + 8/9
bài 1 tính
a) (3/7+-9/8)+(5/8+-6/14)
b) (-5/7+3/11)+(-11/14+14/-11)
c)(-4/5+2/3)+(-5/4+19/5)+(7/3.2)
d)9/16.13/4-9/4.5/16+9/16.17/4
14 : ( 4 2/3 - 1 5/9 ) + 14 : ( 2/3 + 8/9 )
Câu trả lời:
80.8888888889
Học tốt nhé
##No.^^Moon^^##
\(14:\left(4\frac{2}{3}-1\frac{5}{9}\right)+14:\left(\frac{2}{3}+\frac{8}{9}\right)\)
\(=14:\frac{28}{9}+14:\frac{3}{4}\)
\(=14\times\left(\frac{9}{28}+\frac{4}{3}\right)\)
\(=14\times\frac{27}{112}=\frac{27}{8}\)
Câu hỏi :
14 : ( 4 2/3 - 1 5/9 ) + 14 : ( 2/3 + 8/9 )
Câu trả lời :
14 : ( 4 2/3 - 1 5/9 ) + 14 : ( 2/3 + 8/9 ) = 80,8888888889
CHÚC BẠN HỌC TỐT NHA ^_^
1/2+2/3+3/4+4/5+5/6+6/7+7/8+8/9+9/10+10/11+11/12+12/13+13/14+14/15=?
1. Tính
a, 11/15 + - 7/10 + 13/30
b, 7/9 + -1/4 + 3/5
c, -5/21 + -5/14 + 4/35
d, 2/7 + 1/9 + 1/7 + 5/9 + 8/14
e, -4/9 + 8/15 + -2/11 + 5/-9 + 7/15
Tính nhanh
A)-3/7+5/13-4/7+8/13
B)-5/14-2/-14+1/8+1/8
C)-5/13-(3/5+3/13-4/10)
D)[1/8-9/7+4/6-12/7-1/2)+5/9]
a, \(\frac{-3}{7}+\frac{5}{13}-\frac{4}{7}+\frac{8}{13}\)
\(=\frac{-3}{7}-\frac{4}{7}+\frac{5}{13}+\frac{8}{13}\)
\(=-\frac{7}{7}+\frac{13}{13}=-1+1=0\)
b, \(\frac{-5}{14}-\frac{2}{-14}+\frac{1}{8}+\frac{1}{8}\)
\(=\frac{-5}{14}+\frac{2}{14}+\frac{1}{8}+\frac{1}{8}\)
\(=-\frac{3}{14}+\frac{1}{4}=\frac{1}{28}\)
c,\(-\frac{5}{13}-\left(\frac{3}{5}+\frac{3}{13}-\frac{4}{10}\right)\)
\(=-\frac{5}{13}-\frac{3}{13}-\frac{3}{5}+\frac{4}{10}\)
\(=-\frac{8}{13}-\frac{3}{5}+\frac{4}{10}=-\frac{79}{65}+\frac{4}{10}=-\frac{53}{65}\)
d, \(\left[\left(\frac{1}{8}-\frac{9}{7}+\frac{4}{6}-\frac{12}{7}-\frac{1}{2}\right)+\frac{5}{9}\right]\)
\(=\left[\left(\frac{1}{8}-\frac{9}{7}+\frac{2}{3}-\frac{12}{7}-\frac{1}{2}\right)+\frac{5}{9}\right]\)
\(=\left[\left(\frac{1}{8}-\frac{1}{2}-\frac{9}{7}-\frac{12}{7}+\frac{2}{3}\right)+\frac{5}{9}\right]\)
\(=-\frac{65}{24}+\frac{5}{9}=-2\frac{11}{72}\)
a)-3/7+5/13-4/7+8/13
=-3/7-4/7+5/13+8/13
=-7/7+13/13
=-1+1
=0
Tính:
a) \(\dfrac{1}{7}+\dfrac{2}{7}+\dfrac{3}{7}\) b) \(\dfrac{2}{9}+\dfrac{5}{9}+\dfrac{8}{9}\)
c) \(\dfrac{13}{14}-\dfrac{5}{14}-\dfrac{1}{14}\) d) \(\dfrac{7}{11}-\dfrac{4}{11}-\dfrac{3}{11}\)
2/3 = 2 x 4/ 3 x 4 =......../.........
8/14 = 8 : 2/ 8 : 2/ 14 : 2 =........./..........
5/9 = 5 x......./ 9 x 3 =......../.........
35/ 40 = 35 : 5/ 40 : ............. =......./...........
giúp mình với trả lời mình tick cho nhé
2/3 = 2 x 4/ 3 x 4 =8/12
8/14 = 8 : 2/ 14 : 2 =4/7
5/9 = 5 x3/ 9 x 3 =15/37
35/ 40 = 35 : 5/ 40 : 5=7/8
Tính:
a) -5/7(14/5 - 7/10) : |-2/3| - 3/4(8/9 + 16/3) + 10/3(1/3 + 1/5)
b) 17/-26(1/6 - 5/3) : 17/13 - 20/3(2/5 - 1/4) + 2/3(6/5 - 9/2)
c) -8/9(9/8 - 3/2) + 5/4 : (5/2 - 15/4) - 3/4(10/9 - 8/3) : (-1/3)
d) 21/10 : (12/5 - 9/10) . (-4/7) - 3/2(1/6 - 7/12) + 1/5(3/2 - 1/4)
a) Ta có: \(\dfrac{-5}{7}\left(\dfrac{14}{5}-\dfrac{7}{10}\right):\left|-\dfrac{2}{3}\right|-\dfrac{3}{4}\left(\dfrac{8}{9}+\dfrac{16}{3}\right)+\dfrac{10}{3}\left(\dfrac{1}{3}+\dfrac{1}{5}\right)\)
\(=\dfrac{-5}{7}\cdot\dfrac{3}{2}\cdot\dfrac{21}{10}-\dfrac{3}{4}\cdot\dfrac{56}{3}+\dfrac{10}{3}\cdot\dfrac{8}{15}\)
\(=\dfrac{-9}{4}-14+\dfrac{16}{9}\)
\(=\dfrac{-1621}{126}\)
b) Ta có: \(\dfrac{17}{-26}\cdot\left(\dfrac{1}{6}-\dfrac{5}{3}\right):\dfrac{17}{13}-\dfrac{20}{3}\left(\dfrac{2}{5}-\dfrac{1}{4}\right)+\dfrac{2}{3}\left(\dfrac{6}{5}-\dfrac{9}{2}\right)\)
\(=\dfrac{-17}{26}\cdot\dfrac{13}{17}\cdot\dfrac{-3}{2}-\dfrac{20}{3}\cdot\dfrac{3}{20}+\dfrac{2}{3}\cdot\dfrac{-33}{10}\)
\(=\dfrac{3}{4}-1-\dfrac{11}{5}\)
\(=-\dfrac{49}{20}\)
(-5) + (-7) + (-8) + (-3) =
(-4)+((-2)+(-5)+(-6)=
(-8)+(-11)+(-4)+(-2)=
(-9)+((-15)+(-6)+(-3)=
(-12)+(-9)+(-3)+(-8)=
(+3)+(+11)+(+14)+(+7)=
(+9)+(+5)+(+14)+(+2)=
(+12)+(+10)+(+3)+(+5)=
(+4)+(+7)+(+12)+(+15)=
(+20)+(+14)+(+3)+(+7)=
ai lam minh tick cho
a: =-5-7-8-3=-26
b: =-4-2-5-6=-17
c: =-8-11-4-2=-25
d: -9-15-6-3=-30
e: =-12-9-3-8=-32